Gender education in the framework of Ki Hadjar Dewantara’s thought: A literature study and its relevance - Nurdin, Iqbal; Pratiwi, Poerwanti Hadi; Murod, Purnama Hanan (LITERA, 2025)
Gender education is one of the efforts to promote the welfare of humanity. Many institutions prioritize the empowerment of women as a key solution to overcoming disparities between women and men in various fields. This study aims to analyze the educational thoughts of Ki Hadjar Dewantara through his work, Tembang Macapat Wasita Rini. Content analysis of Tembang Macapat Wasita Rini highlights the importance of education for women in achieving both physical and spiritual independence, self-mastery, and preparing women to make decisions in their lives that benefit their families and communities. This poem also contains moral messages urging women to maintain themselves in accordance with societal norms, thereby avoiding various dangers and being able to empower themselves according to their potential. Ki Hadjar Dewantara demonstrated wisdom in responding to the development of education in his time by supporting the ideal of women’s emancipation, balanced with an emphasis on the importance of upholding norms and values aligned with women’s natural roles within the social and cultural context of that era.